Make and Show - United States. Office of Education (Atomic energy here to stay, 1949)
Article illustrating and describing the potential for atomic energy as a subject in high school science exhibits. This is a magazine supplement meant to inform the educational leaders of the United States about the need for schools to address atomic energy with their students. It frames atomic energy as the future of the economy and challenges schools to train the students for this future economy. Cover shows a patient drinking a radioisotopic substance for medical diagnosis.
Keywords: Technology and state; Nuclear energy; Nuclear energy--Research; Nuclear energy--Social aspects; Education